Knowledge and attitudes regarding perinatal infections among pregnant women in Singapore: a cross-sectional study - Chong, Jia Y.; Kadir, Hanis B. A.; Partana, Pamela S.; Tan, Vic K. J.; Yang, Liying (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cytomegalovirus (CMV), toxoplasma and listeria infections during pregnancy can result in devastating consequences and lifetime burden on parents and child. No vaccines are available. Risk of acquiring infections may reduce with greater awareness of preventive measures that can be undertaken during pregnancy and periconceptional period. This is the first study in Singapore to evaluate the knowledge and awareness of perinatal infections. No public health campaigns were done about perinatal infections and they are not routinely included in prenatal discussion. The aim of this study is to understand knowledge and attitudes of pregnant women regarding perinatal infections to better direct preventive efforts. Methods: 400 pregnant respondents from two maternity outpatient units in Singapore completed the questionnaire. Univariate logistic regression analysis was performed to investigate relationship between knowledge levels and sociodemographic variables. Results: Awareness of CMV (17.5%), toxoplasmosis (25.2%) and listeria (24.3%) infections was very low. In addition, while women with young children (OR 1.02, 95% CI 0.58-1.77) and those in childcare-related occupations (OR 0.47, 95% CI 0.16-1.13) are at higher risk of acquiring CMV during pregnancy, they were no better informed than respondents without these risk factors. Women aware of CMV remained poorly informed about risks and preventive methods with almost half being unable to identify risk-reducing measures. Knowledge of preventive measures against toxoplasma and listeria infections was higher but still incomplete. Only 52% of respondents received information about precautionary measures, although most (83.5%) indicated they would have liked to receive more information. Conclusions: Our findings highlight urgent need to improve educational efforts to increase awareness of these infections and preventive measures.